THE EFFECT OF GLYPHOSATE AND PARAQUAT HERBICIDE USE ON THE MORTALITY OF BANDOTAN WEEDS (AGERATUM CONYZOIDES) IN OIL PALM PLANTATIONS - Bornok Adrian Siallagan; Aulia Djuanda Djaingsastro (RADJA PUBLIKA, 2026)
This study aimed to evaluate the effect of glyphosate and paraquat herbicides on the mortality rate of bandotan (Ageratum conyzoides) weeds in oil palm plantations. The study used a non-factorial Randomized Block Design (RBD) with 8 treatments and 3 replications, namely glyphosate (0.4, 0.5, 0.6 mL/L) and paraquat concentration (0.2, 0.3, 0.4 mL/L), as well as a control without herbicide. Observations were made for 15 days after application (HSA) based on visual changes in leaves and weed mortality rates. The results showed that the control treatment had a low weed mortality rate of 0.71 up to 15 HSA. All herbicide treatments significantly increased weed mortality. Paraquat showed the fastest response, where treatment P3 (0.4 mL/L) reached a mortality rate of 8.78 at 3 HSA and a maximum of 10.02 at 4-5 HSA. Meanwhile, glyphosate worked more slowly but remained effective, with the G3 treatment (0.6 mL/L) achieving maximum weed mortality (10.02) at 13-15 HSA. Increasing the dosage of both herbicides was positively correlated with accelerated weed mortality. Overall, paraquat was superior in accelerating weed mortality, while glyphosate was more effective in long-term control. However, the use of paraquat should be limited due to its potential environmental and health impacts. Therefore, glyphosate is recommended as a more sustainable alternative, provided appropriate dosage and application timing are used.